2005
DOI: 10.1016/j.febslet.2005.03.056
|View full text |Cite
|
Sign up to set email alerts
|

Water and molecular chaperones act as weak links of protein folding networks: Energy landscape and punctuated equilibrium changes point towards a game theory of proteins

Abstract: Water molecules and molecular chaperones efficiently help the protein folding process. Here we describe their action in the context of the energy and topological networks of proteins. In energy terms water and chaperones were suggested to decrease the activation energy between various local energy minima smoothing the energy landscape, rescuing misfolded proteins from conformational traps and stabilizing their native structure. In kinetic terms water and chaperones may make the punctuated equilibrium of confor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 56 publications
(133 reference statements)
0
63
0
Order By: Relevance
“…Nevertheless, some ideas in that direction have been put forward (most of them for biophysical applications, though). For example, Kovács et al [55] suggested that the binding of two proteins to give a protein complex can be regarded as a "game" in which both proteins have two possible strategies. Elaborating on their ideas, one could imagine that each of the proteins can be either flexible or rigid.…”
Section: Game Theory and Biophysicsmentioning
confidence: 99%
“…Nevertheless, some ideas in that direction have been put forward (most of them for biophysical applications, though). For example, Kovács et al [55] suggested that the binding of two proteins to give a protein complex can be regarded as a "game" in which both proteins have two possible strategies. Elaborating on their ideas, one could imagine that each of the proteins can be either flexible or rigid.…”
Section: Game Theory and Biophysicsmentioning
confidence: 99%
“…However, members of this Hsp family are constitutively present in cells. The induced and the constitutively expressed Hsp families are well known as molecular chaperones which help in normal folding of various polypeptides, assist misfolded proteins to attain or regain their native states, regulate protein degradation, and help in translocation of proteins to different cellular compartments (Hartl and Hayer-Hartl 2002;Kovacs et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is sufficient that these multi-target drugs affect their targets only partially, which corresponds well with the presumed low-affinity interactions of these drugs with several of their targets [16,31,32]. It has been summarized before that weak links (low-probability, low-intensity edges) stabilize complex systems [33,34]. Here we showed a kind of reverse statement: that multiple, weak hits efficiently confuse the integrity of complex systems.…”
Section: Discussionmentioning
confidence: 80%